Advances in drug delivery applications of modified bacterial cellulose-based materials - Liang, Shuya (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial cellulose (BC) is generated by certain species of bacteria and comprises of polysaccharide with unique physical, chemical and mechanical characteristics. Due to its outstanding biocompatibility, high-purity, excellent mechanical strength, high water absorption and highly porous structure, BC has been recently investigated for biomedical application. However, the pure form of BC is hardly used as biomedical materials due to its some inherent shortcomings. To extend its applications in drugs delivery, modifications of native BC are widely used to improve its properties.Usually, BC modifications can be done by physical, chemical and biological modifications. In this review, a brief introduction of BC and its production and fabrication are first displayed, these set a stage for up to date and in depth discussions of modification. Finally, we focus on the potential applications of BC as drug delivery system.